The innocent murmurs - Ahmad H. Asdie Ahmad H. Asdie (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1981)
In this article the innocent murmur includes only those murmurs that are associated with no known abnormality, either structural or physiologic. The term